jianglyFans's blog

By jianglyFans, history, 4 years ago, In English

zscoder introduced Generating functions in Competitive Programming in his blog, which give a method to get the formula of general term of a array by it's generating function.

But sometime the generating function is somewhat complicated, for instance, the array http://oeis.org/A054726 which has generating function:

$$$ 1 + \frac{3}{2} z - z^2 - \frac{z}{2} \sqrt{1 - 12 z + 4 z^2} $$$

and we can calculate the first n term by poly sqrt with fft in $$$O(n \log n)$$$

But this array have a recurrence formula:

$$$ a_{n} = \frac{ (12 n - 30) a_{n-1} - (4 n - 16) a_{n-2} }{n-1} $$$

which will be much easy to calculate.

My question is how can I get recurrence formula by it's generating function in general(or some special form) ?


I know how to do this now, thanks qwaszx who give me a hint.

If $$$f(z) = p(z)^{ \frac{1}{m} }$$$ is generating function of $$$a_n$$$, where $$$p(z)$$$ is a polynomial. then

$$$ p(z) f'(z) = \frac{1}{m} p(z) p'(z) $$$

compare the coefficient of $$$z^n$$$, and we will get the recurrence formula of $$$a_n$$$

Let us calculate the above example: $$$f(z) = 1 + \frac{3}{2} z - z^2 - \frac{z}{2} \sqrt{1 - 12 z + 4 z^2}$$$

let $$$b_n = a_{n+1}$$$ and $$$g(z)$$$ is generating function of $$$b_n$$$, then

$$$ g(z) = \sum_{n = 0} ^{\infty} a_{n+1} z ^ {n} = \frac{ f(z) - f(0)}{z} = \frac{3}{2} - z - \frac{1}{2} \sqrt{1 - 12 z + 4 z^2} $$$

so we get differential of $$$g(z)$$$

$$$ g'(z) = -1 - \frac{2z - 3}{\sqrt{1 - 12 z + 4 z^2}} = \frac{3-2z - \sqrt{1 - 12 z + 4 z^2}}{\sqrt{1 - 12 z + 4 z^2}} $$$

and

$$$ \begin{align} (1 - 12z + 4 z^2) g'(z) &= (3-2z - \sqrt{1 - 12 z + 4 z^2}) (\sqrt{1 - 12 z + 4 z^2}) \\ &= (3 - 2z) (3-2z - 2g(z)) - (1 - 12z + 4 z^2) \\ &= (4z - 6) g(z) + 8 \end{align} $$$

compare the coefficient of $$$z^n$$$, we have $$$(n + 1)b_{n+1} - 12 n b_n + 4(n-1)b_{n-1} = 4 b_{n-1} - 6 b_n$$$, so

$$$ (n+1)a_{n+2} = (12 n - 6) a_{n+1} - (4n - 8) a_n $$$

so we archive our goal: $$$a_{n} = \frac{ (12 n - 30) a_{n-1} - (4 n - 16) a_{n-2} }{n-1}$$$

Full text and comments »

  • Vote: I like it
  • +15
  • Vote: I do not like it